Faits d’actualité - D., J. (Assurances)

(untitled) (HEC Montréal, 1983)
The writer describes here some personal ideas on various subjects: the computer and thought; a recent statement concerning life insurance policies written before 1970; the advantages and disadvantages of personalized office hours. He also describes the future of the American market as seen by a speaker at the American College of Bryn Mawr; the problems of cash flow in reinsurance, the confusion caused by a recent judgment of the Court of Appeal concerning a claim against a third party for automobile insurance; an inventory of personal effects and, finally, the insurance results in Canada during the first three months of 1982.